Numerical thermal performance of free convection in metal foam heat sinks with fin edges (University of Thi-Qar Journal for Engineering Sciences, 2020)
This study introduces numerical investigation of natural convection in metal foam heat sinks with two types of fin edges namely fillet and sharp edges. Aluminum metal foam of various pore densities (5, 10, 20 PPI) and sets of porosities ( ) are used in the simulations. The dimensions of the samples were 100 mm length, 100 mm height, 10 mm thickness and the spacing between fins were kept at 8 mm. Then the metal foam strips were installed onto an aluminum base plate (100 * 100 * 3.5 mm3). The investigation has been performed by control volume method . As well as, the energy equations are established on a principle that based on a local thermal non-equilibrium (LTNE) model in which the temperature of the fluid and the solid matrix are solved separately. The heat input was different from 4 to 30 W in numerical runs and the air was used as a working fluid. The results show that the base temperature of the heat sink is lower for the new design of edges. Therefore, the proposed approach of the heat sink has significant potential to be utilized to enhance the thermal performance of heat sinks and thereby to develop more advanced effective cooling devices and techniques. The maximum enhancement of the heat transfer coefficient with fillet profile reached 5.6% greater than fins with sharp edges